2022
DOI: 10.1111/jan.15160
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of Australian Maternal and Child Health home visiting nurses undertaking family violence work: An interpretive description study

Abstract: Aims To explore the family violence practice of home visiting nurses and identify the personal and professional characteristics of nurses undertaking family violence work. Design A qualitative research design using interpretive description. Methods The family violence nursing practice and characteristics of home visiting nurses in Victoria, Australia, were explored by analysing semi‐structured interviews (n = 37) conducted over 4 months in 2019–2020. Twenty‐five nurses and 12 nurse managers worked in urban, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…They had to prioritize their time, felt alone in their work, and were burdened by their responsibility. This is consistent with several previous studies, where lack of time, the balance of risk and support and loneliness were highlighted (Adams et al, 2022;Dahlbo et al, 2017). Dahlbo et al (2017) studied paediatric nurses and found that their work to prevent child maltreatment often led to feelings of powerlessness and thoughts about children that persisted even after working hours.…”
Section: Discussionsupporting
confidence: 93%
“…They had to prioritize their time, felt alone in their work, and were burdened by their responsibility. This is consistent with several previous studies, where lack of time, the balance of risk and support and loneliness were highlighted (Adams et al, 2022;Dahlbo et al, 2017). Dahlbo et al (2017) studied paediatric nurses and found that their work to prevent child maltreatment often led to feelings of powerlessness and thoughts about children that persisted even after working hours.…”
Section: Discussionsupporting
confidence: 93%
“…Nurses working with families enrolled in population‐specific home visitation programmes, including the Nurse‐Family Partnership® (NFP) programme, often develop long‐term therapeutic relationships with their clients and provide holistic client‐centred care that prioritizes improving multiple prenatal, maternal, and child health outcomes. For this reason, nurse home visitors are in an optimal position to identify women experiencing intimate partner violence (IPV) and then intervene to support women in increasing safety for themselves and their children (Adams et al, 2022). This qualitative process evaluation, which was part of an overall evaluation of an NFP IPV intervention using a cluster‐based, single‐blind randomized controlled trial (RCT), was conducted to understand the implementation of this IPV intervention and to identify factors influencing its use by nurses in their home visiting practice.…”
Section: Introductionmentioning
confidence: 99%